2011
DOI: 10.1093/bioinformatics/btr614
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic priors for identifying active transcription factor binding sites

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
121
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 28 publications
4
121
0
Order By: Relevance
“…Using machine learning methods, 43 these predictions can be used to identify TFs acting as key regulators [4,46,47]. 44 In addition to open-chromatin data, also Histone Modification (HM) ChIP-seq data 45 was used for the prediction of TF binding [4,5,13,24,51,67]. In these studies, HMs were 46 used either exclusively or along with open-chromatin data.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Using machine learning methods, 43 these predictions can be used to identify TFs acting as key regulators [4,46,47]. 44 In addition to open-chromatin data, also Histone Modification (HM) ChIP-seq data 45 was used for the prediction of TF binding [4,5,13,24,51,67]. In these studies, HMs were 46 used either exclusively or along with open-chromatin data.…”
mentioning
confidence: 99%
“…It was shown that using 47 DNaseI-seq data alone can lead to highly accurate TF binding predictions [13,51], 48 therefore we mainly focus on open-chromatin data in this article. 49 There are two general classes of methods to predict TF binding: site-centric 50 methods [13,32,42,51,57,69], and segmentation-based methods [3,7,24,25,27,48,50,58]. 51 Site-centric methods require the identification of putative TF binding sites (TFBS) 52 using TF binding motifs represented with position weight matrices (pwms).…”
mentioning
confidence: 99%
See 3 more Smart Citations